KERJASAMA INDONESIA-AUSTRALIA MELALUI PROGRAM INOVASI DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI JAWA TIMUR (PERIODE 2018 - 2020) - Hanifa Nada Fajriyani, (2023)
The quality of education plays a crucial role in producing highly competitive human resources. However, in Indonesia, the quality of education remains relatively low, as evidenced by low student learning outcomes and high illiteracy rates in several provinces, including East Java. Given the challenges of the global era, it is imperative for the government to prioritize the issue of education quality, particularly in terms of literacy and numeracy skills. To address this, Indonesia has partnered with Australia through the INOVASI program, which focuses on improving early grade student learning outcomes. This research aims to identify and analyze the implementation of Indonesia-Australia cooperation through the INOVASI program in East Java, utilizing a descriptive qualitative research method. The study also incorporates theories and concepts of international cooperation and foreign aid as analytical instruments. Through the collaboration between Indonesia and Australia via the INOVASI program, efforts to enhance education quality and improve student learning outcomes can be realized. This collaboration serves as an instrumental approach to achieving better education quality, which ultimately impacts the Human Development Index (HDI).